The implementation of lateral trunk motion in two-dimensional video analysis during unipodal functional screening tests in elite female athletes - Dingenen, B.; Malfait, B.; Verschueren, S.; Staes, F. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Two-dimensional (2D) video analysis is a valid and reliable method to measure knee valgus (KV) during functional screening tests (Munro et al., 2011). However, focusing only on this angle may be too limited and may lead to misinterpretations when assessing knee injury risk, as it is recognized that the lower extremity acts as a linked system of interdependent segments. Increased ipsilateral trunk motion (LTM) during unipodal tasks may influence hip adduction (HA) and knee abduction loading and therefore increase knee injury risk in female athletes (Hewett and Myer, 2011). The purpose of this study was to implement the measurement of LTM in 2D video analysis, and to examine the relationship between LTM, HA and KV during unipodal functional screening tests. Methods: A total of 63 elite female athletes (35 soccer, 16 handball and 12 volleyball) who were injury- and pain free were tested (age: 21.28 ± 3.36 years). LTM, HA and KV were measured during the deepest phase of the single-leg drop vertical jump (SLDVJ) and single-leg squat (SLS) with a standard digital camera. Smaller angles represent more LTM, HA and KV. Pearson correlations coefficients were calculated between angles within and between tests. Results: In the SLDVJ test, LTM was significantly correlated with HA (r=-0.537; p<0.001) and KV (r=-0.254; p=0.045). In the SLS test, LTM was significantly correlated with HA (r=-0.527; p<0.001) and KV (r=-0.367; p=0.004). Furthermore, LTM (r=0.315; p=0.015), HA (r=0.396; p=0.002) and KV (r=0.407; p=0.001) were significantly correlated between SLS and SLDVJ. Discussion: The results of the present study show that more LTM is significantly correlated with less HA and KV during unipodal screening tests, suggesting that LTM can be used as a compensation mechanism for poor hip and knee control. As a consequence, focusing only on KV angles can mimic knee injury risk, as an increased LTM can increase knee abduction load. The combination of more LTM and more KV, may lead to the highest knee injury risk (Hewett et al., 2009). Furthermore, the amount of LTM, HA and KV was significantly correlated between the SLS and SLDVJ. This indicates that in general the same strategy was used to complete both tasks. These results support the fact that the knee does not function as an isolated joint, but as a part of the kinetic chain. Therefore, we suggest to implement the measurement of LTM in the 2D video analysis of functional screening tests.